Integration of Deep Learning in Teaching Local Wisdom Values in Islamic Education - Dwi Fajri, Muhammad; Amrin (Mimbar Agama Budaya, 2025)
This study explores applying deep learning technology to enhance the teaching of local wisdom values in Islamic education. In the artificial intelligence era, integrating its capabilities in education is on the rise, but teaching local wisdom has not yet kept up with modern technology. A qualitative approach with a literature review focused on the application of deep learning in Islamic education is addressed in this study. The survey results show that deep learning can create adaptive learning systems that tailor the materials based on students' characteristics. Such systems can enrich learners ' experiences, enhance understanding of Islamic values, and improve younger learners' character development through local wisdom, Islamic teachings, and ethics more efficiently. Other possibilities include automated analysis of students' learning behaviors for personalized instruction, easy interaction with the educational materials, and learning through experiences. Therefore, integrating deep learning technology into Islamic education could offer innovative approaches to guard and disseminate teaching local wisdom in light of modern technological advancements.